A centennial catalogue of hydro-geomorphological events and their atmospheric forcing - da Silva Pereira, Susana (2020)
The DISASTER database records 1969 unique hydro-geomorphologic cases (floods and landslides) that generated human damages in Portugal during a 150 year-period (1865–2015. The main purposes of this work are the following: to present a national disaster events catalogue; to analyse the atmospheric conditions and to discuss the role of rainfall as main driving force of the hydro-geomorphological disaster events. The main Circulation Weather Types (CWTs) and the presence of Atmospheric Rivers (ARs) of each day of the disaster events were classified using the 20CR dataset (1865–2014) and the NCEP/NCAR reanalysis (2015). These datasets were used to compute the daily cumulative precipitation and the long term climatological year accumulated precipitation 10th, 50th, 90th and 95th percentile spanning 1865–2015 and the accumulated rainfall conditions after and before each disaster event. In the central and northern Portugal Disaster events are mainly driven by southwest (SW), west (W), northwest (NW) and Cyclonic (C) Weather Types, whereas the CWTs with a southern and eastern component [east (E), southeast (SE) and south (S)] are the main drivers in the south part of the country. Cyclonic CWT is widely associated with convective systems that can generate flash floods and urban floods often responsible for fatalities and injured people. CWTs with a westerly component can be associated to prolonged wet periods that can induce flood events in the main rivers and landslides in the mountain areas. The methodology used to build this disaster event catalogue can be applicable to other study areas, namely the North Atlantic and the Mediterranean regions, where the flood and landslides extremes are related to the atmospheric circulation.